Congenital aortic valve stenosis: from pathophysiology to molecular genetics and the need for novel therapeutics - Yasuhara, Jun; Schultz, Karlee; Bigelow, Amee M.; Garg, Vidu (Frontiers in Cardiovascular Medicine, 2023)
Congenital aortic valve stenosis (AVS) is one of the most common valve anomalies and accounts for 3%–6% of cardiac malformations. As congenital AVS is often progressive, many patients, both children and adults, require transcatheter or surgical intervention throughout their lives. While the mechanisms of degenerative aortic valve disease in the adult population are partially described, the pathophysiology of adult AVS is different from congenital AVS in children as epigenetic and environmental risk factors play a significant role in manifestations of aortic valve disease in adults. Despite increased understanding of genetic basis of congenital aortic valve disease such as bicuspid aortic valve, the etiology and underlying mechanisms of congenital AVS in infants and children remain unknown. Herein, we review the pathophysiology of congenitally stenotic aortic valves and their natural history and disease course along with current management strategies. With the rapid expansion of knowledge of genetic origins of congenital heart defects, we also summarize the literature on the genetic contributors to congenital AVS. Further, this increased molecular understanding has led to the expansion of animal models with congenital aortic valve anomalies. Finally, we discuss the potential to develop novel therapeutics for congenital AVS that expand on integration of these molecular and genetic advances.